2009
DOI: 10.1007/s12664-009-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of steatosis after interferon therapy in HCV genotype 4 is related to weight loss

Abstract: Steatosis is common in genotype 4 HCV infection, and its presence appears to be related to high BMI, but not to viral load or degree of liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
3
6
1
Order By: Relevance
“…Our study revealed that steatosis was present in 56.1% of patients similar the prevalence reported by earlier studies that included all genotypes or HCV genotype four alone…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study revealed that steatosis was present in 56.1% of patients similar the prevalence reported by earlier studies that included all genotypes or HCV genotype four alone…”
Section: Discussionsupporting
confidence: 91%
“…In the present study steatosis remains stationary in half of the population and only improved in quarter of the patients three months post treatment with DAAs. A previous study by Esmat et al which reported the changes in hepatic steatosis after pegylated interferon and ribavirin therapy in Egyptian patients. They found that steatosis grade improved in 42.9% of their patients, 45.7% had no change in their steatosis grade while 11.4% only showed worsening of their steatosis grade.…”
Section: Discussionmentioning
confidence: 96%
“…We also found that body mass index was significantly higher in the group with steatosis than in the group without steatosis by histopathology. These findings are inconsistent with the finding of other studies in our country 21–23. Due to the increased incidence of HCV, limitations of biopsy, and development of reliable noninvasive blood tests, liver biopsy should no longer be considered mandatory for screening of liver lesions in the first instance.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been assumed by other authors that viral load may be involved in the pathogenesis of steatosis in HCV-infected patients 21. accordingly, in our study, there was a trend towards higher viral load in patients with steatosis as detected by liver biopsy, and there was a significant positive correlation between viral load and steatosis by FibroMax.…”
Section: Discussionsupporting
confidence: 74%
“…In the first report by Khattab et al on 131 HCV-G4 patients, steatosis was associated with insulin resistance measured by homeostatic model assessment (HOMA), BMI, waist circumference, serum triglycerides, serum cholesterol, systolic hypertension, and histological scores of inflammation and fibrosis [12]. On the other hand, in the other study also on HCV-G4 Egyptian patients, Esmat et al concluded that the presence of steatosis correlated with BMI but not to viral load, grade of inflammation, or stage of fibrosis [13]. On follow up, they found that improvement in steatosis was significantly associated with the degree of weight loss but not with response to anti-viral treatment.…”
Section: Discussionmentioning
confidence: 97%